An edge-based smoothed point interpolation method for elasto-plastic coupled hydro-mechanical analysis of saturated porous media. (February 2017) - Ghaffaripour, O.; Khoshghalb, A.; Khalili, N.
Abstract: An edge-based smoothed point interpolation method is adopted for coupled hydro-mechanical analysis of saturated porous media with elasto-plastic behaviour. A novel approach for the evaluation of the coupling matrix of the porous media is adopted. Stress integration is performed using the substepping method, and the modified Newton-Raphson approach is utilised to address the nonlinearities arising from the elasto-plastic constitutive model used in the formulation. Numerical examples are studied and the results are compared with analytical solutions and those obtained from the conventional finite element method (FEM) to evaluate the performance of the proposed model.